Hubungan Antara Fleksibilitas Trunk Dengan Keseimbangan Pada Lanjut Usia - Ayu Putri Mayang Sari, Attika, Wahyuni, SSt.FT.M.Kes, Umi Budi Rahayu, SSt. Ft. SPd. M. Kes (2015)
Being old is a process that can not be avoided by everyone. In the elderly or the elderly many changes with age, decrease in musculoskeletal system is the flexibility of the trunk. Trunk flexibility is the ability of the joints to move or bend the trunk joint or multiple joints without a hitch. When the trunk flexibility impaired then the center of gravity on the body will experience changes in postural alignment is no longer in the supporting foundation so that the body can not maintain posture response so consequently there was a balance disorder. This study aims to investigate the relationship between trunk flexibility with balance in the elderly. This research has been conducted in IHC Setia Kawan Elderly and Elderly IHC Tomb of Haji Menur VI on 6 and 8 May 2015. This type of observation study with Cross Sectional approach. The study population numbered 80 people, samples that meet the inclusion and exclusion criteria of 60 people. The data obtained are not normally distributed, statistical test Chi Square test. Results of the data analysis show the value │p = 0,001│ or p <0,05 so Ho rejected and Ha accepted. So that there is a relationship between trunk flexibility with the balance in the elderly. Hopefully this research can provide information to the public, especially in the elderly in order to be able to grow old with more healthy.